Efektifitas Kombinasi Murottal Al-Qur’an dan Aromaterapi Lavender terhadap Gangguan Tidur Pada Pasien Hemodialisa - Alvian Ainurrofiq Dwi Putranto; Ari Budiati Sri Hidayati; Indri Setiya Wati (MES Bogor, 2025)
Patients with chronic kidney disease (CKD) undergoing hemodialysis often experience sleep disturbances as one of their complaints, which can significantly reduce their quality of life. The aim of this study was to evaluate the effectiveness of a complementary therapy combining the recitation (murottal) of Surah Ar-Rahman with lavender aromatherapy in improving the sleep quality of hemodialysis patients. The study was conducted on a 60-year-old CKD patient in the inpatient ward of PKU Muhammadiyah Gamping Hospital over five consecutive days. The intervention was administered each night for 10–20 minutes before bedtime. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). The results showed a significant decrease in the PSQI score, from a score of 10 indicating poor sleep quality to a score of 1 indicating good sleep quality on the fifth day. This study demonstrates that the combination of murottal and lavender aromatherapy is effective in improving sleep quality in CKD patients undergoing hemodialysis, making it a safe and beneficial non-pharmacological intervention in nursing practice.